Hiperglikemia sebagai prediktor kondisi kaki pada pasien Diabetes Mellitus - Dheni Koerniawan; Sanny Frisca (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
The condition of the feet of DM patients is one of the indicators that must be studied in monitoring the incidence of ulcers. In DM patients, ulcer problems can occur as a result of vascular and neurological damage. Both causes are initiated through poor metabolic control as assessed by blood glucose levels. The purpose of this study is to analyze several factors that are theoretically and empirically related to the condition of the feet. This cross-sectional study was conducted on the DM group in Palembang city (n = 50), by filling out a characteristic questionnaire, examining foot conditions, and measuring fasting blood sugar levels. The research findings revealed that of all the factors tested with Kendall Tau, blood sugar levels were the only one that was significant (p-value = 0.002) so that it could be significant as a predictor of the condition of the feet. Controlling these levels is important in controlling the incidence of ulcers in patients. The next step that can be taken is to carry out a thorough examination of the patient's neurovascular condition with the Ankle Brachial Index (ABI) and the Michigan Neuropathy Screening Instrument (MNSI).